Avaliação da sustentabilidade dos agroecossistemas de agricultores familiares que atuam na feira-livre de Pato Branco - PR - Silva, Marivânia Rufato da (2015)
Currently, an environmental crisis poses challenges to humanity towards sustainable development. Especially the Brazilian rural areas, from the 90's, increased research and the defense of family farming as an option for sustainable rural development. In this context, the sustainability evaluation processes are considered important allies for decision making and management of sustainability in family agro-ecosystems. Thus, we defined the objective for this research to evaluate the sustainability level of agro-ecosystems of family farmers who work in the open-air market of Pato Branco- PR. To attend the above objective, there was a case study with a sample of 10 agroecosystems of family farmers who work in the open-air market. To operationalize the evaluation process of sustainability were: (i) identified 133 indicators proposed in previous national surveys; (ii) conducted validation of indicators considered as appropriate to the context, in the perception of technical managers organs and of the farmers responsible for agro-ecosystems; (iii) selected 37 sustainability indicators, grouped into dimensions social, environmental and economic. Data collection was performed by means of semi-structured interviews with farmers responsible for each agro-ecosystem and the data analysis is qualitative. The results show a general level of sustainability of 2.3 on a scale of 1 to 3, composed of environmental sustainability levels of 2.2, social de 2.2 and by the level of economic sustainability 2.4. This value, according to the established scale, reflects a level of sustainability between regular and high, which suggests that the agro-ecosystems are sustainable, but actions can be performed mainly for nine indicators with compromising performance, in order to improve sustainability economic, environmental and social group.